2006
DOI: 10.1364/josab.23.000593
|View full text |Cite
|
Sign up to set email alerts
|

Long-term frequency instability of atomic frequency references based on coherent population trapping and microfabricated vapor cells

Abstract: We present an evaluation of the long-term frequency instability and environmental sensitivity of a chip-scale atomic clock based on coherent population trapping, particularly as affected by the light-source subassembly. The long-term frequency stability of this type of device can be dramatically improved by judicious choice of operating parameters of the light-source subassembly. We find that the clock frequency is influenced by the laser-injection current, the laser temperature, and the rf modulation index. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Thus, for cPT-based atomic clocks, the detection noise can be noticeably reduced. In such a case, v mod is larger than the line width Γ of the monitored signal 3 [13], [14], which cannot be implemented in the microwave optical double resonance (dr) clock scheme as presently used. on the contrary, in reference [13], the authors showed that it is possible to realize a cPT clock using v mod ≈ 10 · Γ.…”
Section: Coherent Population Trapping Vapor Cellmentioning
confidence: 99%
“…Thus, for cPT-based atomic clocks, the detection noise can be noticeably reduced. In such a case, v mod is larger than the line width Γ of the monitored signal 3 [13], [14], which cannot be implemented in the microwave optical double resonance (dr) clock scheme as presently used. on the contrary, in reference [13], the authors showed that it is possible to realize a cPT clock using v mod ≈ 10 · Γ.…”
Section: Coherent Population Trapping Vapor Cellmentioning
confidence: 99%
“…There has been much interest recently in the effect of the propagation of a laser beam through dilute vapors of alkali metal atoms [1][2][3][4][5] due to their application in laser cooling [6,7], chip-scale atomic clocks and magnetometers [8,9], laser stabilization [10][11][12], and electromagnetically induced transparency [13]. In order to understand the spectra, several models have been proposed which accurately predict the Doppler-broadened and sub-Doppler absorption spectra of a dilute vapor with weak and strong probe beams [1,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the coherent population trapping (CPT) phenomenon [1,2] has drawn more and more attention in the time and frequency community. The possibility of using the CPT phenomenon for the implementation of atomic clocks was proposed in the last decade, and experiments are currently being carried out on several laboratories [3][4][5][6][7][8][9][10][11] . Portable atom clock with small volume has been in demand for portable equipment such as GPS and BEIDOU receivers, in-field telecommunication devices, and various kinds of measuring instruments.…”
mentioning
confidence: 99%